Vaccine display on artificial bacterial spores enhances protective efficacy against Staphylococcus aureus infection. Issue 18 (30th July 2018) - Karauzum, Hatice; Updegrove, Taylor B; Kong, Minsuk; Wu, I-Lin; Datta, Sandip K; Ramamurthi, Kumaran S
Abstract: Spores of Bacillus subtilis are encased in a protein coat composed of ∼80 different proteins. Recently, we reconstituted the basement layer of the coat, composed of two structural proteins (SpoVM and SpoIVA) around spore-sized silica beads encased in a lipid bilayer, to create synthetic spore-like particles termed 'SSHELs'. We demonstrated that SSHELs could display thousands of copies of proteins and small molecules of interest covalently linked to SpoIVA. In this study, we investigated the efficacy of SSHELs in delivering vaccines. We show that intramuscular vaccination of mice with undecorated one micron-diameter SSHELs elicited an antibody response against SpoIVA. We further demonstrate that SSHELs covalently modified with a catalytically inactivated staphylococcal alpha toxin variant (Hla H35L ), without an adjuvant, resulted in improved protection against Staphylococcus aureus infection in a bacteremia model as compared to vaccination with the antigen alone. Although vaccination with either Hla H35L or Hla H35L conjugated to SSHELs similarly elicited the production of neutralizing antibodies to Hla, we found that a subset of memory T cells was differentially activated when the antigen was delivered on SSHELs. We propose that the particulate nature of SSHELs elicits a more robust immune response to the vaccine that results in superior protection against subsequent S. aureus infection. Abstract : Delivery of a vaccine on artificial bacteria increased the efficacy of the vaccine against Staphylococcus aureus infection.